15% bandwidth 7 GHz GaN‐MMIC Doherty amplifier with enhanced auxiliary chain. Issue 2 (February 2014) - Piazzon, Luca; Colantonio, Paolo; Giannini, Franco; Giofré, Rocco
ABSTRACT This contribution presents the development and characterization of a GaN Doherty power amplifier for backhaul microwave links in the 6.35–7.35 GHz frequency range. To minimize the AM/AM distortion, a driver stage is integrated in the auxiliary branch. Such feature also allows to obtain a higher overall gain than the standard approach. Moreover, to enlarge the bandwidth a coupled lines directional coupler is adopted at the input to split the power to the two branches. Experimental characterization showed 10.5 dB Gain, 38.1 dBm saturated output power, 42% efficiency at 7 dB output back‐off, and 15% bandwidth at 1 dB gain ripple. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:502–504, 2014